Efforts to Prevent Crime Triggers in Sexual Murder Cases in China Through Public Education, Victim Protection, Perpetrator Rehabilitation, and Law Enforcement - Jiahui, Xinyue (Fakultas Syariah INSURI Ponorogo, 2024)
This study aims to provide evidence-based recommendations for public education, victim protection, offender rehabilitation, and law enforcement. Adopting a literature review methodology, this research analyzes sexual homicides in China to identify the factors that trigger such crimes and the strategies to prevent them. Through literature searches, document studies, and expert interviews, this study highlights the profiles of perpetrators, who are predominantly males with troubled pasts and often possess antisocial or schizoid personality disorders. Victims are often chosen randomly, with extreme physical and sexual violence used to express dominance. This phenomenon reflects broader social dysfunctions in Chinese society and challenges within the judicial system. The investigation of these cases underscores the need for a multidisciplinary approach to understand and prevent sexual crimes. This work emphasizes the importance of prevention strategies based on criminological theories such as Power and Control, Sexual Violence and Aggression, and Criminological Psychopathology to holistically address the issue of sexual homicide.